2013
DOI: 10.1111/plb.12096
|View full text |Cite
|
Sign up to set email alerts
|

Comparing simple root phenotyping methods on a core set of rice genotypes

Abstract: Interest in belowground plant growth is increasing, especially in relation to arguments that shallow-rooted cultivars are efficient at exploiting soil phosphorus while deep-rooted ones will access water at depth. However, methods for assessing roots in large numbers of plants are diverse and direct comparisons of methods are rare. Three methods for measuring root growth traits were evaluated for utility in discriminating rice cultivars: soil-filled rhizotrons, hydroponics and soil-filled pots whose bottom was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…In general it is reported that rooting depth of rice accessions differs between subpopulations. For example Shrestha et al (2014) report that rhizotron screens rank subgroups in the order aus  >  tropical japonica  >  indica  ≈  temperate japonica for maximum root length which was in agreement with an earlier report of Lafitte et al (2001). This order has been confirmed testing the RDP1 with the herbicide screen (unpublished results) where aus has the highest average scores, followed by tropical japonica with indica and temperate japonica both similarly low.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In general it is reported that rooting depth of rice accessions differs between subpopulations. For example Shrestha et al (2014) report that rhizotron screens rank subgroups in the order aus  >  tropical japonica  >  indica  ≈  temperate japonica for maximum root length which was in agreement with an earlier report of Lafitte et al (2001). This order has been confirmed testing the RDP1 with the herbicide screen (unpublished results) where aus has the highest average scores, followed by tropical japonica with indica and temperate japonica both similarly low.…”
Section: Discussionsupporting
confidence: 83%
“…6) whereas the strongest correlation for shoot traits was with shoot length at day 35 ( r  = 0.586). Figure 6 shows that check varieties behaved as expected (as shown in Shrestha et al 2014), with Black Gora very long rooted, Azucena reasonably long rooted, IR 64 reasonable short rooted and Bala very short rooted. There were Sri Lankan landraces across the spectrum of these check varieties including some very long and very short rooted.
Fig.
…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…As an alternative, two dimensional (2D) root imaging in rhizotrons enables the quantification of root growth along the interface between soil and a transparent cover. This method is amenable to high throughput and provides very comprehensive information on root system architecture with limitations on tall plants or late developmental stages (Nagel et al 2012;Shrestha et al 2014).…”
Section: Introductionmentioning
confidence: 99%